Rewriting Shakespeare: Shakespeare’s early modern readers at work - Jean-Christophe Mayer (Etudes Epistémè)
While Shakespeare may have written solely for the stage, his text has been configured and transformed since the sixteenth century by the print cycle, which enabled it to survive. This was a cycle in which readers, publishers, as well as other interpreters of Shakespeare’s text played an important role. In this article, I look at the important work of renovation of the printed text accomplished by early modern readers of Shakespeare’s editions. Whether they worked inside books or whether they made manuscript books (commonplace books, miscellanies, diaries) out of printed editions, their task, to some extent, was never to reach completeness. But it was never synonymous with failure for all that. Individually and as a whole, the open-endedness of their venture meant that, however partial their efforts, their way of relating to texts continued to be informed by a genuine interest in past writings and by a strong desire to invent a future for them. In writing themselves thanks to Shakespeare, they rewrote Shakespeare and allowed others to write themselves through Shakespeare’s texts. In addressing these issues, I am using manuscript and printed material from the Folger Shakespeare Library, Washington, DC.